Intrauterine Diagnosis and Treatment of High‐Grade Atrioventricular Block: A Case Series and Literature Review - Alireza Golbabaei; Elham Sadat Alavi Moghaddam; Mahsa Naemi; Hooman Mohammad Talebi (Clinical Case Reports)
ABSTRACT Early and timely intervention can restore normal fetal heart rhythm in cases of high‐grade atrioventricular block without structural abnormalities. However, the presence of complications like cardiomyopathy significantly worsens the prognosis, despite aggressive treatment. Multidisciplinary care and close monitoring are essential to optimize maternal and fetal outcomes.